Pengaruh Latihan Menggunakan Media Paralon Terhadap Keterampilan Pointing Posisi Jongkok Jarak 8 Meter Pada Pemain Petanque IKIP PGRI Pontianak - Rahima, Pida; Arifin, Zainal; Asmutiar (Universitas PGRI Pontianak, 2023)
This research aims to find out: (1) To find out the effect of pointing skills at a distance of 8 meters before being given training using paralon media on IKIP PGRI Pontianak petanque players. (2) To determine the effect of pointing skills at a distance of 8 meters after being given training using paralon media to IKIP PGRI Pontianak petanque players. (3) To find out whether there is an influence on the ability to point at a distance of 8 meters on petanque players at IKIP PGRI Pontianak. This type of research is experimental research and the form used is a pre-experimental design with a one group pretest-posttest design research plan. The population in this study were 15 IKIP PGRI Pontianak pétanque players. The data analysis technique in this research uses descriptive and inferential statistics. The instruments used in this research were pre-test (initial test) and post-test (final test). The test result data is then analyzed through hypothesis testing with analysis of one paired sample. The results of the research show that there is an influence of training using paralon media on the skills of pointing a squatting position at a distance of 8 meters in petanque players at IKIP PGRI Pontianak, obtained a t_count value of 27.521 with a t_table value of 2.144 and a Sig of 0.05..